Wild-Type, but Not Mutant N296H, Human Tau Restores Aβ-Mediated Inhibition of LTP in Tau−/− mice - Vargas-Caballero, Mariana; Denk, Franziska; Wobst, Heike J.; Arch, Emily; Pegasiou, Chrysia-Maria; Oliver, Peter L.; Shipton, Olivia A.; Paulsen, Ole; Wade-Martins, Richard (Frontiers in Neuroscience, 2017)
Microtubule associated protein tau (MAPT) is involved in the pathogenesis of Alzheimer’s disease and many forms of frontotemporal dementia (FTD). We recently reported that Aβ-mediated inhibition of hippocampal long-term potentiation (LTP) in mice requires tau. Here, we asked whether expression of human MAPT can restore Aβ-mediated inhibition on a mouse Tau-/- background and whether human tau with an FTD-causing mutation (N296H) can interfere with Aβ-mediated inhibition of LTP. We used transgenic mouse lines each expressing the full human MAPT locus using bacterial artificial chromosome technology. These lines expressed all six human tau protein isoforms on a Tau-/- background. We found that the human wild-type MAPT H1 locus was able to restore Aβ42-mediated impairment of LTP. In contrast, Aβ42 did not reduce LTP in slices in two independently generated transgenic lines expressing tau protein with the mutation N296H associated with frontotemporal dementia (FTD). Basal phosphorylation of tau measured as the ratio of AT8/Tau5 immunoreactivity was significantly reduced in N296H mutant hippocampal slices. Our data show that human MAPT is able to restore Aβ42-mediated inhibition of LTP in Tau-/- mice. These results provide further evidence that tau protein is central to Aβ-induced LTP impairment and provide a valuable tool for further analysis of the links between Aβ, human tau and impairment of synaptic function.